THE EFFECT OF MINDFULNESS THERAPY AS A STRATEGY FOR STRESS PREVENTION AND MANAGEMENT IN WORKERS: A SYSTEMATIC REVIEW - Yuniarti, Tanti; Permatasari, Henny; Permata Sari, Indah (Indonesian Journal of Community Health Nursing, 2026)
Introduction: Work-related stress is a common concern in contemporary work environments, affecting employees physical and psychological health. It is essential to identify effective interventions to mitigate stress and its associated health risks. Mindfulness-based interventions (MBIs) have gained attention as promising methods for stress reduction and mental health improvement. This systematic review examines the effectiveness of Mindfulness therapy for stress prevention among workers.   Method: A systematic review following Joanna Briggs Institute recommendations. The databases searched were PubMed, Science Direct, ProQuest and Sage Journal. Search was conducted in February 2025. The review synthesizes evidence from recent studies published between 2020 and 2025. Keywords used included 'Mindfulness therapy,' 'stress prevention,' 'occupational stress,' and 'worker well-being.' The inclusion criteria encompassed focusing on adult workers aged 18 to 60. Articles not involving workers or focusing on non-occupational stress were excluded.   Result: A total of 14 studies were included, comprising randomized controlled trials, meta-analyses, systematic reviews and observational studies. Findings consistently demonstrated that Mindfulness interventions, such as Mindful Breathing, Mindfulness Meditation, and Body Scan Meditation, effectively reduce stress levels among workers. The results support the adoption of Mindfulness-based practices in occupational health programs. Implementing Mindfulness interventions in the workplace could reduce stress and enhance employee well-being. However, some studies reported variability in the effectiveness based on intervention duration and participant engagement   Conclusion: Mindfulness therapy is a viable strategy for preventing occupational stress. Further research is recommended to explore long-term effects and optimize intervention delivery in diverse workplace settings.   Keywords: Mindfulness, occupational health nursing, stress;worker